The Relationship between Remittances and Social Development in Mogadishu – Somalia - Simiyu, Edwin Jairus; Ismail Omar, Mohamed; Mugano, Gift (2017)
The study investigated the relationship between remittance and Social Development in Mogadishu-Somalia. Social development was measured through development indicators on health and education paying key attention on the intervening variables such as Political instability, insecurity, inflation rate, the exchange rate and changing policies on remittance. This study adopted a none-experimental case study design using quantitative and qualitative approaches on a sample population of 399 respondents who receive and do not receive remittance in Mogadishu capital city of Somalia. Data was collected using a questionnaire and analyzed using SPSS computer software. This study noted that remittance had a significant positive relationship with social development and it predicted 31.7% of the variance in social development. There was a significant difference between those who received remittance and those who do not receive remittance in relation to social development. This study recommended that the government of Somalia should provide microeconomic policies and enabling environments relating to remittance and its utilization in accessing education, health services, improved income and employment creation. Finally this study found it necessary that the Somalia government should put measures to manage the influence political instability, insecurity, inflation rate, exchange rates and remittance policies that indirectly Social development in Somalia.